INFLUENCE OF CORE STABILITY EXERCISE ON CORE STRENGTH FLEXIBILITY AND CORE STRENGTH ENDURANCE AMONG CRICKET MEN - PHANEENDRA, Dr.V.V.M.U.; SUBRAHMANAYAM, V. (ShodhKosh: Journal of Visual and Performing Arts, 2023)
The purpose of the study was to find out the Influence of core stability exercise on core strength, flexibility and core strength endurance among Cricket men. To achieve this purpose of the study twenty four men players were selected from the Government College, Rajahmundry, AndhraPradesh, India were selected and their age ranged from 18 to 24 years. for this study. The age of the subject was ranged from 18 to 24 years. The selected subjects were assigned at random into two group of 12 subjects each (N=12) group1 underwent core stability exercise training for six weak and three days per week. Group2 acted as control group. However, control group was not exposed to any specific training but they participated in the regular schedule. The present study was undertaken primarily to assess the core stability exercise on core strength, flexibility and core strength endurance among adolescence men. The collected data from all the two groups were statistically analysis. To find out the significant improvement between the pre and post test means dependent t test was used as statistical techniques. To find out significant adjusted post test difference among the group. Analysis of covariance (ANCOVA) was used. As the two groups were involved, whenever the f-ratio was found to be significant. In all cases the criterion for statistical significance was at 0.05level was fixed. . The experimental group namely core stability training group have achieved significant improvement on core strength, flexibility and core strength endurance when compared to control group. Significant differences were found between core stability training and control group towards improving the selected variables such as core strength, flexibility and core strength endurance.